THE INVESTIGATION OF PECULIARITIES STUDENTS’ INDEPENDENT WORK - A. P. Preobrazhenskiy (Science and Innovation Center Publishing House, 2019)
The paper analyzes the independent work of students. The results of application of electronic technologies in independent work are given.